Predictive value of early EEG for seizures in neonates with hypoxic–ischemic encephalopathy undergoing therapeutic hypothermia. (September 2018) - Cornet, Marie-Coralie; Pasupuleti, Archana; Fang, Annie; Gonzalez, Fernando; Shimotake, Thomas; Ferriero, Donna; Glass, Hannah Cranley; Cilio, Maria Roberta
Abstract Objectives To assess the prognostic significance of an early normal/mildly abnormal conventional EEG (cEEG) on seizure risk in neonates undergoing therapeutic hypothermia. Methods We reviewed the video-EEG recordings from a large cohort of neonates treated with therapeutic hypothermia for hypoxic–ischemic encephalopathy from 2008 to 2017 in a single tertiary center. Continuous video-EEG was started as soon as possible (median 8.2 h) and continued throughout hypothermia and rewarming. We studied those neonates with a normal/mildly abnormal EEG during the first 24 h of monitoring. Results A total of 331 neonates were treated with hypothermia and 323 had cEEG recordings available for review; 99 were excluded because of a moderately/severely abnormal cEEG background and/or seizure during the first 24 h of recording, and an additional eight because of early rewarming. The remaining 216 had a normal/mildly abnormal cEEG in the first 24 h. None of these patients subsequently developed seizures. Conclusion A normal/mildly abnormal cEEG during the first 24 h indicates a very low risk of subsequent seizures. This suggests that cEEG monitoring can be safely discontinued after 24 h if it has remained normal or excessively discontinuous and no seizures are detected, limiting the need for this resource-intensive and expensive tool.